PG81 In situ simulation of surgical patient processes during the early onset of Covid19. (10th November 2020) - Ward, Jeremy; Shetty, Vinutha; Krishnamohan, Nitya; Tabassum, Amir; Ingleson, Laura
Abstract : Background: The advent of Covid19 brought rapid changes in practice and new standard operating procedures (SOPs). We ran sessions for surgical ward and theatre staff to become familiar with new processes and pathways, to assess their practicability in the clinical environment and to come to standardised processes. Summary of Work: In situ simulation sessions were organised for staff on surgical wards and in theatre, working through a range of scenarios appropriate to that team. For ward staff this included admission process, management of possible Covid19 infection, as well as theatre processes, including consent, documentation and transfer. In theatre the scenarios included team brief, PPE plans, theatre set up, patient transfer and peri-operative processes. These sessions were separate to other simulations of new technical procedures Summary of Sessions/Results: We ran 5 sessions for ward staff involving a total of 48 participants, and 6 sessions for 44 theatre staff. The distribution of staff is shown in the attached table 1 . Discussion and Conclusions/Recommendations: As the Covid19 pandemic approached NHS staff were beset by multiple new procedures, often coming in 'at pace, ' which led to confusion and differences in application between teams. Whereas much simulation covered specific technical procedures we focussed on basic aspects of the patient pathway which still caused confusion. Involving a wide range of medical/nursing staff enabled wide scrutiny of new SOPs and discussion about their practicability in the clinical setting, introducing any required changes. It also helped standardisation between teams. This was crucial to successful implementation and developing a culture of adaptation to future change. It was also helpful in reducing hierarchy. This supports the importance of in situ simulation in the introduction of new procedures to assess their practicability as well as in educating staff about such changes.